Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To solve this problem, follow these steps:
1. Determine the slope of the given line:
The equation of the given line is [tex]\( 3y + 4x = 7 \)[/tex]. We can rewrite this in the slope-intercept form [tex]\( y = mx + b \)[/tex].
[tex]\[ 3y + 4x = 7 \implies 3y = -4x + 7 \implies y = -\frac{4}{3}x + \frac{7}{3} \][/tex]
Therefore, the slope [tex]\( m \)[/tex] of the given line is [tex]\( -\frac{4}{3} \)[/tex].
2. Find the slope of the perpendicular line:
The slope of the line that is perpendicular to another line is the negative reciprocal of the original slope. Thus, the slope of the perpendicular line is:
[tex]\[ m_{\text{perpendicular}} = -\frac{1}{-\frac{4}{3}} = \frac{3}{4} \][/tex]
3. Use the point-slope form to find the equation of the perpendicular line:
The point-slope form of a line's equation is [tex]\( y - y_1 = m(x - x_1) \)[/tex], where [tex]\( (x_1, y_1) \)[/tex] is a point on the line and [tex]\( m \)[/tex] is the slope.
Given point [tex]\((4, -3)\)[/tex] and slope [tex]\( \frac{3}{4} \)[/tex]:
[tex]\[ y - (-3) = \frac{3}{4}(x - 4) \implies y + 3 = \frac{3}{4}(x - 4) \][/tex]
4. Simplify the equation:
Distribute the slope on the right-hand side:
[tex]\[ y + 3 = \frac{3}{4}x - \frac{3}{4} \cdot 4 \][/tex]
[tex]\[ y + 3 = \frac{3}{4}x - 3 \][/tex]
Subtract 3 from both sides to isolate [tex]\( y \)[/tex]:
[tex]\[ y = \frac{3}{4}x - 3 - 3 \][/tex]
[tex]\[ y = \frac{3}{4}x - 6 \][/tex]
Thus, the equation of the line passing through [tex]\((4, -3)\)[/tex] and perpendicular to the line [tex]\( 3y + 4x = 7 \)[/tex] is:
[tex]\[ y = \frac{3}{4}x - 6 \][/tex]
1. Determine the slope of the given line:
The equation of the given line is [tex]\( 3y + 4x = 7 \)[/tex]. We can rewrite this in the slope-intercept form [tex]\( y = mx + b \)[/tex].
[tex]\[ 3y + 4x = 7 \implies 3y = -4x + 7 \implies y = -\frac{4}{3}x + \frac{7}{3} \][/tex]
Therefore, the slope [tex]\( m \)[/tex] of the given line is [tex]\( -\frac{4}{3} \)[/tex].
2. Find the slope of the perpendicular line:
The slope of the line that is perpendicular to another line is the negative reciprocal of the original slope. Thus, the slope of the perpendicular line is:
[tex]\[ m_{\text{perpendicular}} = -\frac{1}{-\frac{4}{3}} = \frac{3}{4} \][/tex]
3. Use the point-slope form to find the equation of the perpendicular line:
The point-slope form of a line's equation is [tex]\( y - y_1 = m(x - x_1) \)[/tex], where [tex]\( (x_1, y_1) \)[/tex] is a point on the line and [tex]\( m \)[/tex] is the slope.
Given point [tex]\((4, -3)\)[/tex] and slope [tex]\( \frac{3}{4} \)[/tex]:
[tex]\[ y - (-3) = \frac{3}{4}(x - 4) \implies y + 3 = \frac{3}{4}(x - 4) \][/tex]
4. Simplify the equation:
Distribute the slope on the right-hand side:
[tex]\[ y + 3 = \frac{3}{4}x - \frac{3}{4} \cdot 4 \][/tex]
[tex]\[ y + 3 = \frac{3}{4}x - 3 \][/tex]
Subtract 3 from both sides to isolate [tex]\( y \)[/tex]:
[tex]\[ y = \frac{3}{4}x - 3 - 3 \][/tex]
[tex]\[ y = \frac{3}{4}x - 6 \][/tex]
Thus, the equation of the line passing through [tex]\((4, -3)\)[/tex] and perpendicular to the line [tex]\( 3y + 4x = 7 \)[/tex] is:
[tex]\[ y = \frac{3}{4}x - 6 \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.